Sinus Microbiota in Patients With Eosinophilic and Non-Eosinophilic Chronic Rhinosinusitis With Nasal Polyps - Feng, Tingting; Miao, Ping; Liu, Bin; Liu, Yao; Bao, Ximing; Xu, Ji; Ren, Nana; Li, Ying; Shi, Jiali; Cao, Wanxin; Fang, Jianchen; Li, Min; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by Th2-skewed inflammation and increased colonization by Staphylococcus aureus. CRSwNP can be distinguished with Eosinophilic (ECRSwNP) and Non-eosinophilic (NECRSwNP) by the infiltration of eosinophils. The local microbiota plays an important role in the persistent inflammation of CRSwNP. To evaluate the bacterial community composition on the distinct types of CRSwNP patients, we collected nasal swabs from 16 ECRSwNP patients, 18 NECRSwNP patients and 39 Healthy control subjects. The microbiome structure for all the samples were analyzed by high-throughput 16SrRNA gene sequencing. Concentration of S. aureus were determined using TaqMan quantitative polymerase chain reaction (qPCR) targeting the nuclease (nuc) gene. The result showed significant differences in the sinus microbiome among Healthy control subjects and CRSwNP patients. Microbiota community diversity was significantly lower in NECRSwNP samples compared to that of Healthy control subjects. Interestingly, the abundance of several pathogenic bacteria was diverse between ECRSwNP and NECRSwNP patients. Although Staphylococcus prevailed in all in CRSwNP group and Healthy control groups, the abundance of Staphylococcus is significantly higher in Health control group than ECRSwNP group whereas Corynebacteriaceae were predominant in ECRSwNP patients. More important, the abundance of S. aureus was much higher in NECRSwNP patients This study highlights that microbiota composition may attribute to the different clinical types of CRSwNP, inspiring new therapeutic strategies to resolve this chronic inflammation process.